The low carbon economy : understanding and supporting a sustainable transition - Baranova, Polina; Conway, Elaine; Lynch, Nicola; Paterson, Fred (Palgrave Macmillan, 2017)
This edited collection explores the challenges and opportunities presented by the transition to a low carbon economy, and outlines the different approaches taken to ensure the sustainability of such a transition. Chapters explore the nature of the transformation from a 'brown' to 'green' economy, the importance of effective carbon measurement and management methodologies, the use of behaviour economics, and the application of a growth-enabling approach. Offering valuable insights into how various stakeholders respond to the challenges of green growth and focusing in particular on the support of universities, The Low Carbon Economy covers themes of leadership, systems approach, stakeholder management, and collaborative action. This comprehensive study provides readers with constructive ideas for maximising the opportunities of transitioning to a low carbon economy, and will serve as a useful tool for practitioners and academics interested in sustainability.
Keywords: Sustainable development.; Social responsibility of business.; elektronické knihy; electronic books